Neonatal maternal separation opposes the facilitatory effect of castration on the respiratory response to hypercapnia of the adult male rat: Evidence for the involvement of the medial amygdala. (18th December 2017) - Tenorio‐Lopes, L.; Henry, M. S.; Marques, D.; Tremblay, M.‐È.; Drolet, G.; Bretzner, F.; Kinkead, R.
Abstract : Respiratory manifestations of panic disorder (PD) include a greater respiratory instability and enhanced responsiveness to CO2 compared to normal individuals. Although the prevalence of PD is approximately three times greater in women compared to men, the origins of this sexual dimorphism remain poorly understood. Similar to PD patients, adult female rats previously subjected to neonatal maternal separation (NMS) show an increase in their ventilatory response to CO2 . Because this effect of NMS is not observed in males, we hypothesised that testosterone prevents NMS‐induced hyper‐responsiveness to CO2 . Pups subjected to NMS were placed in an incubator for 3 h d ‐1 from postnatal days 3‐12. Control pups remained undisturbed. At adulthood (8‐10 weeks of age), rats were then subjected either to sham surgery or castration. Fourteen days later, breathing was measured at rest (room air) and during acute exposure to hypercapnia (5 and 10% CO2 for 10 minutes each) using plethysmography. To gain insight into the mechanisms involved, c‐fos expression was used as an indicator of neuronal activation. Brains were collected following air or CO2 exposure for quantification of c‐fos positive cells by immunohistochemistry in selected regions, including the paraventricular nucleus of the hypothalamus, the dorsomedial hypothalamus and the amygdalar complex. Castration produced a 100% increase of hyperventilatory response to 10% CO2 in control rats. Unexpectedly, castration had no effect on the hyperventilatory response of NMS rats. The intensity of the hypercapnic response was inversely correlated with c‐fos expression in the medial amygdala. We conclude that testosterone prevents the hyper‐responsiveness to CO2, whereas NMS attenuates sensitivity to hormone withdrawal. We propose that an inhibitory influence from the medial amygdala contributes to this effect.